Bracon zuleideae Perioto & Lara (Hymenoptera, Braconidae): seed predation potential, expansion of the geographic distribution and new data on host plant phenology - Perioto, Nelson Wanderley; Lara, Rogéria Inês Rosa; Versuti, Danielle Roberta (EntomoBrasilis, 2019)
Abstract. Here, by the first time, was quantified the predation of seeds of Protium ovatum Engl. (Burseraceae) by Bracon zuleideae Perioto & Lara (Hymenoptera, Braconidae), a phytophagous seed eater, in Parque Nacional Grande Sertão Veredas, located in the State of Minas Gerais, Brazil. B. zuleideae is now mentioned for the state of Minas Gerais, Brazil, which extends its geographical distribution about 900 km north of its type locality, its only previous record, and new data about host plant phenology are provided. Bracon zuleideae Perioto & Lara (Hymenoptera, Braconidae): potencial de predação de sementes, expansão da distribuição geográfica e novos dados de fenologia da planta hospedeira Resumo. A predação de sementes de Protium ovatum Engl. (Burseraceae) por Bracon zuleideae Perioto & Lara (Hymenoptera, Braconidae) foi quantificada pela primeira vez no Parque Nacional Grande Sertão Veredas, em Minas Gerais, Brasil. A distribuição geográfica de B. zuleideae é estendida para o Estado de Minas Gerais, Brasil, a cerca de 900 km ao norte da localidade tipo, o único registro anterior, e novos dados sobre a fenologia da planta hospedeira são fornecidos.